BERHERMENEUTIK BERSAMA DERRIDA - Udang, Frety Cassia (Institut Agama Kristen Negeri Manado, 2019)
Humans are interpretive beings; a creature that is always seeking meaning and understanding reality outside of himself. The process of understanding and understanding continues and is productive as long as humans are and exist in this life. As long as there is an effort to interpret and understand, hermeneutics play a role. This paper tries to see hermeneutic understanding as a means of criticizing the absoluteness and dominance of meaning and understanding from the perspective of Derrida Deconstruction. Hermeneutics in the perspective of deconstruction provides important space for readers and their context in constructing meaning. The various meanings and understandings are appreciated as a necessity of a process of reading texts. Through Derrida's glasses, deconstruction becomes a reflective tool to open new awareness and new possibilities, which may have been missed in the effort to understand